2019
DOI: 10.1108/ebr-12-2016-0168
|View full text |Cite
|
Sign up to set email alerts
|

Dialogic features of brand South Africa’s website and tourists’ intentions to visit

Abstract: Purpose Despite the recognisable importance of nation brand websites, they have seemingly not been the focus of dialogic communication interrogations of marketing and communications scholars. This paper is one of the initial attempts to address such research lacuna. The paper aims to examine the dialogic potential of the Brand South Africa website and its effect on the country’s image, as well as the impact of this image on consumers’ (tourists) visiting intentions. Design/methodology/approach Drawing from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Along with technological developments, communication to build relationships with the public is also done through websites, so dialogic communication principles should be attached to the website's content as well (Kent and Taylor, 1998;Oliveira and Huertas, 2014;Pang et al 2018). Other research revealed that the more an organisation incorporates dialogic principles through its website, the more likely it can foster an interactive relationship with the public (Hinson, et al 2019).…”
Section: University Library Website and Principles Of Dialogic Commun...mentioning
confidence: 99%
See 1 more Smart Citation
“…Along with technological developments, communication to build relationships with the public is also done through websites, so dialogic communication principles should be attached to the website's content as well (Kent and Taylor, 1998;Oliveira and Huertas, 2014;Pang et al 2018). Other research revealed that the more an organisation incorporates dialogic principles through its website, the more likely it can foster an interactive relationship with the public (Hinson, et al 2019).…”
Section: University Library Website and Principles Of Dialogic Commun...mentioning
confidence: 99%
“…Several studies in various types of organizations have proven that websites could potentially establish dialogic communication because of their ability to combine one-way mass communication and two-way interpersonal communication (Hinson et al 2019;Ingenhoff and Koelling, 2010;Kent and Taylor, 1998). At least, this dialogic communication can cover the absence of face-to-face communication due to the policy of maintaining social distancing during a pandemic.…”
Section: University Library Website and Principles Of Dialogic Commun...mentioning
confidence: 99%